Effect of Bacterial Population from Rhizosphere of Various Foliage Plants on Removal of Indoor Volatile Organic Compounds - Chun, S.C., Konkuk University, Seoul, Republic of Korea; Yoo, M.H., Konkuk University, Seoul, Republic of Korea; Moon, Y.S., Konkuk University, Seoul, Republic of Korea; Shin, M.H., Konkuk University, Seoul, Republic of Korea; Son, K.C., Konkuk University, Seoul, Republic of Korea; Chung, I.M., Konkuk University, Seoul, Republic of Korea; Kays, Stanley J., University of Georgia, Athens, GA, USA (Weon'ye gwahag gi'sulji, 2010)
Total bacterial populations were cultured from the Hydroball cultivation media in the rhizospheres of 9 different plants including Hedera helix L. and Dracaena deremensis cv. Warneckii Compacta, etc. These cultured bacterial populations were studied to test if the bacterial populations in the plant growing pots may play a role on removal of volatile organic compounds (VOCs) such as benzene and toluene in the air. To meet this objective, first, we tested the possibility of removal of VOCs by the cultured total bacteria alone. The residual rates of benzene by the inoculation of total bacterial populations from the different plant growth media were significantly different, ranging from 0.741-1.000 of Spathiphyllum wallisii 'Regal', Pachira aquatica, Ficus elastica, Dieffenbachia sp. 'Marrianne' Hort., Chamaedorea elegans, compared to the control with residual rate of 0.596 (LSD, P=0.05). This trend was also similar with toluene, depending on different plants. Based on these results, we inoculated the bacterial population cultured from P. aquatica into the plant-growing pots of P. aquatica, F. elastica, and S. podophyllum inside the chamber followed by the VOCs injection. The inoculated bacteria had significant effect on the removal of benzene and toluene, compared to the removal efficacy by the plants without inoculation, indicating that microbes in the rhizosphere could play a significant role on the removal of VOCs along with plants.